The Effect of Profitability, Liquidity, and Capital Structure on Firm Value - Wijaya, Andreanno Septian Eka; Andarwati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This quantitative causal research departed from the decreasing value of food and beverage companies during the 2020-2023 period. The objective is to identify the effects of profitability, liquidity, and capital structure on firm value by studying food and beverage manufacturing companies listed on the Indonesia Stock Exchange. It employs secondary data acquired from 28 companies selected through saturation sampling technique. The data analysis was performed using multiple linear regression in SPSS for Windows version 30. This study finds that profitability has positive and significant effects on the firm value, while liquidity and capital structure negatively and significantly influence the firm value. In this model, profitability, liquidity, and capital structure can explain firm value.